Trace metal emission history captured in a Chilean ice core. (1st May 2022) - Potocki, Mariusz; Dixon, Daniel A.; Kurbatov, Andrei V.; Casassa, Gino; Zamora, Rodrigo; Handley, Michael J.; Introne, Douglas; Grigholm, Bjorn; Korotkikh, Elena V.; Birkel, Sean D.; Clifford, Heather; Mayewski, Paul A.
Abstract: Ice core records provide a robust tool for reconstructing past climate variability and for improving our understanding of the relative contributions of natural and anthropogenic emissions into the atmosphere. In particular, heavy metal pollution from anthropogenic emissions poses a significant health and environmental risk. We present a sub-annually dated, continuously sampled Tupungatito ice core (TPG-12) data set that documents change in atmospheric pollution in Central Chile. Results from our well-preserved environmental record display a significant change in atmospheric pollutant concentrations coincident with anthropogenic activities in this region, notably from Chile. TPG-12 Enrichment factors (EFs) for Cd, As, Pb, Cu, and Ag exhibit values in excess of natural inputs over the last one hundred years, with increases beginning around 1930. Terrestrial source dust elements such as Ce, La, Pr, and Ti do not exhibit similarly increased EF values, demonstrating an anthropogenic source for Cd, As, Pb, Cu, and Ag. Our results also capture a decrease in As and Pb starting in the early 2000s, in concert with new environmental regulations in Chile (Caldentey and Mondschein, 2003). Highlights: Highly detailed, continuous, 100-year record from a Central Chilean ice core. Environmental record displays a significant change in atmospheric pollutants. Rise in heavy metals primarily attributed to anthropogenic activities in this region. The observed decrease suggests the pollution regulations can be effective.